Relationships between heart rate and age, bodyweight and breed in 10, 849 dogs. (11th May 2013) - Hezzell, M. J.; Humm, K.; Dennis, S. G.; Agee, L.; Boswood, A.
Abstract : Objectives: To evaluate relationships between heart rate and clinical variables in healthy dogs and dogs examined at a referral hospital. Methods: Clinical data were extracted from the electronic patient records of a first opinion group (5000 healthy dogs) and a referral hospital (5849 dogs). Univariable and multi‐variable general linear models were used to assess associations between heart rate and clinical characteristics. Separate multi‐variable models were constructed for first opinion and referral populations. Results: In healthy dogs, heart rate was negatively associated with bodyweight (P<0·001) but was higher in Chihuahuas. The mean difference in heart rate between a 5 and 55 kg dog was 10·5 beats per minute. In dogs presenting to a referral hospital, heart rate was negatively associated with bodyweight (P<0·001) and the following breeds; border collie, golden retriever, Labrador retriever, springer spaniel and West Highland white terrier and positively associated with age, admitting service (emergency and critical care, emergency first opinion and cardiology) and the following breeds; Cavalier King Charles spaniel, Staffordshire bull terrier and Yorkshire terrier. Clinical Significance: Bodyweight, age, breed and disease status all influence heart rate in dogs, although these factors account for a relatively small proportion of the overall variability in heart rate.